2016
DOI: 10.1364/boe.7.000542
|View full text |Cite
|
Sign up to set email alerts
|

Toward reliable retrieval of functional information of papillary dermis using spatially resolved diffuse reflectance spectroscopy

Abstract: Spatially resolved diffuse reflectance spectroscopy (SRDRS) has been employed to quantify tissue optical properties and its interrogation volume is majorly controlled by the source-to-detector separations (SDSs). To noninvasively quantify properties of dermis, a SRDRS setup that includes SDS shorter than 1 mm is required. It will be demonstrated in this study that Monte Carlo simulations employing the Henyey-Greenstein phase function cannot always precisely predict experimentally measured diffuse reflectance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…31 The probing region of our DRS con guration contains epidermis and upper dermis of human skin, and thus our system is sensitive to the chromophore and structural variation in this skin region. 32 We found that, in the wavelength range from 500 to 900 nm, while the oxygenated and deoxygenated hemoglobin concentrations of psoriatic skin were distinct from those of normal sites, other skin functional parameters, such as melanin, collagen, and reduced scattering coe cients, did not show statistically signi cant difference between the psoriatic and normal sites. 15 However, using the skin hemoglobin concentration derived from DRS alone is di cult in achieving effective psoriasis diagnosis or monitoring.…”
Section: Discussionmentioning
confidence: 64%
“…31 The probing region of our DRS con guration contains epidermis and upper dermis of human skin, and thus our system is sensitive to the chromophore and structural variation in this skin region. 32 We found that, in the wavelength range from 500 to 900 nm, while the oxygenated and deoxygenated hemoglobin concentrations of psoriatic skin were distinct from those of normal sites, other skin functional parameters, such as melanin, collagen, and reduced scattering coe cients, did not show statistically signi cant difference between the psoriatic and normal sites. 15 However, using the skin hemoglobin concentration derived from DRS alone is di cult in achieving effective psoriasis diagnosis or monitoring.…”
Section: Discussionmentioning
confidence: 64%
“…Nevertheless, compared to the H&E histology, the SHG intensity image from the collagen structure is clearer. To match the interrogation depth of detection by DRS system, we referred to our previous study, in which Monte Carlo simulation was used to determine the average penetration depth of photon packets with common optical properties . According to different μ a and μ s ′ combinations, the average interrogation depth is 400‐1400 μm.…”
Section: Resultsmentioning
confidence: 99%
“…To match the interrogation depth of detection by DRS system, we referred to our previous study, in which Monte Carlo simulation was used to determine the average penetration depth of photon packets with common optical properties. 23 According to different μ a and μ s ′ combinations, the average interrogation depth is 400-1400 μm. For the SHG intensity integration, we select 6×8 pieces of SHG image (Light Square in Figure 4B tively.…”
Section: Animal Studymentioning
confidence: 99%
“…The probing region of our DRS configuration contains epidermis and upper dermis of human skin, and thus our system is sensitive to the chromophore and structural variation in this skin region 32 . We found that, in the wavelength range from 500 to 900 nm, while the oxygenated and deoxygenated hemoglobin concentrations of psoriatic skin were distinct from those of normal sites, other skin functional parameters, such as melanin, collagen, and reduced scattering coefficients, did not show statistically significant difference between the psoriatic and normal sites 15 .…”
Section: Discussionmentioning
confidence: 99%